Posttraumatic Stress Symptoms Among Chinese College Students During the COVID-19 Pandemic: A Longitudinal Study - Chi, Xinli; Huang, Liuyue; Hall, Daniel L.; Li, Raissa; Liang, Kaixin; Hossain, Md Mahbub; Guo, Tianyou (Frontiers in Public Health, 2021)
A longitudinal assessment of the prevalence posttraumatic stress symptoms (PTSS) and risk factors is indispensable for further prevention and/or treatment. The longitudinal web-based survey enrolled 1,164 college students in China. Measures at two time poits (February and August 2020). PTSS, demographic information, adverse childhood experiences (ACEs), resilience and self-compassion information were collected to explicate the prevalence and predictors of PTSS concurrently and over time. Results showed that although PTSS generally declined throughout the six months after the outbreak of COVID-19, the prevalence remained relatively high. Resilience and self-compassion negatively predicted of PTSS concurrently and longitudinally. While subjective family socioeconomic status (SES) and ACEs at Wave 1 did not predict PTSS under COVID-19 at Wave 1, but both significantly predicted PTSS at Wave 2. Findings implicate potential targets for detecting and intervening on symptoms of trauma in this vulnerable population.